When fixation creates fiction - Miné-Hattab, Judith (eLife, 2023)
A chemical regularly used to image cells can dramatically alter the way cellular compartments called condensates look under the microscope.
Keywords: liquid-liquid phase separation; fixation; live-cell single-molecule imaging; intrinsically disordered proteins; condensates; cross-linking